Evaluation of orientation and efficiency of schoolchildren nutrition in recreational period - Podrigalo, Leonid; Iermakov, Sergii; Rovnaya, Olga; Yermakova, Tetiana; Cieślicka, Mirosława; Muszkieta, Radosław (Progress in Nutrition, 2020)
Background: determination of antioxidant orientation schoolchildren of nutrition in recreational period and evaluation of its efficiency. Methods: it is studied nutrition of 221 schoolchildren aged 7-15 years old at children’s recreational institution. It is used the method of analysis of menu production records with the subsequent calculation of average daily set of foods, specifying its chemical composition and energy value. The efficiency of nutrition was estimated according to indicators of vitamin and antioxidant statuses. The dynamics of excretion of vitamins C, B2 and B6 was studied in hour-long portion of urine. The features of urine bio-chemiluminescence in 9 indicators are estimated. Studies were conducted on 2-3 and 22-23 days of recreation. Result: it is confirmed the existence of antioxidant direction of nutrition by means of sufficient content of total protein, aromatic amino acids, phospholipids, tocopherols, B vitamins, S, Zn. Content of Se, ascorbic acid in food ration was insufficient. It is determined 16 indicators which are most objectively characterized antioxidant direction of food ration. Conclusion: The nutritional factor influenced positively on vitamin and antioxidant status of organism. The determined correlation dependences between indicators of biochemiluminescence and level of vitamins egestion confirmed the efficiency of nutritional factor for influence on schoolchildren’s health.